Experimental studies on differences of penetration between modified suction caisson and regular suction caisson in clay. (7th February 2021) - Li, Dayong; Ma, Shili; Zhang, Yukun; Chen, Fuquan
ABSTRACT: This paper presents results form a series of model tests performed to study penetration behaviour of the modified suction caisson (MSC) in clay. By comparing with the regular suction caisson as a reference, features of MSCs penetration were discovered. The phenomenon of MSCs penetration, the relationships between time, penetration depth, velocity and the required suction were discussed in order to obtain the change in the penetration resistance. When the external skirt touches the mudline, the tip resistance and the shaft frictional force of the MSC increases sharply. Expressions of estimating the resistance to penetrating the MSC was proposed. It was found that when the MSC is penetrated into clay with low shear strength, the penetration resistance obtained by using the proposed method is smaller than the model test result, indicating that the disturbance of the clay induced by the suction-assisted installation cannot be ignored.